Some observations on demography and edible plants of Lion-tailed Macaques (Macaca silenus) in the rain forest fragmented habitats of Anamalai Hills, Western Ghats - K, Narasimmarajan; R, Nagarajan; A, Kumaraguru (Journal of Research in Biology, 2011)
Some observations on demography and edible plants species of endangered Lion-tailed Macaques (LTM) (Macaca silenus) were studied between January 2008 and July 2008 in the rain forest fragments of Annamalai Hills, Southern India. Totally, 14 different fragments were surveyed, in which LTM existence was observed in 10 fragments. LTM were noticed in Iyyerpady, Uralikkal, Chinnakalar, Manompoly, Sekalmudy, Korangumudi, Pannimedu, Varattuparai, Puthuthottam and Andhiparai. 18 different troops of LTM numbering 279 individuals were observed in 10 different fragments. The group size ranged from smallest of five individuals at Pannimedu to highest number of 62 individuals at Puthuthottam. In total, 48 adult males, 86 adult females, 24 sub-adult males, 41 sub-adult females, 49 juveniles and 30 infants were observed for the entire study period. It was observed that the group size and number of troops varied in these fragments which could be attributed to the food availability in each fragments and other factors such as anthropogenic pressures, competition between sympatric primates. Other variations such as diversity of vegetation, mean of tree density, Girth at Breast Height (GBH), canopy spread and tree height noticed in these fragments were also analyzed for their implication on the distribution pattern. Based on this study we give some essential suggestion (1) Ecotourism is one of the serious threats for the LTM populations, (2) People knowingly feeding the plastics and food items to LTMs, which are yet to have existing on the road side. (3) We suggest that tourists traveling between Azhiyar to Valparai should be checked properly with mobile patrol and spot penalty is to be needed (Fig; 2) for the control of these activities